Horizons 2030 : equality at the centre of sustainable development (UN ECLAC SantiagoCL, 2016)
Aims to provide an analytical complement to the 2030 Agenda and the sustainable development goals from a structuralist perspective and the point of view of the Latin American and Caribbean countries.
Includes summary